Stability in Northeast Asia: bolstering defence diplomacy - Singh, Bhubhindar (2013)
Despite the recent escalation of tensions in Northeast Asia sparked by the territorial disputes, these are reasons to argue for its stability. One way is to bolster defence diplomacy between China, Japan and South Korea.